The great pandemics that ravaged Brazil (Research, Society and Development, 2022)
To conduct a survey of national and international literature on the main epidemics and pandemics that have occurred in Brazil and the world. Scoping review was utilized as methodology, conducted from a qualitative historiographical approach, bringing a historically organized discussion of the main pandemics that hit humanity. As a result, the convergence of fields in public health, public policies and the necessity of creating structure for the prevention and the combat against pandemics were listed. It is concluded that the pandemic cycles faced by humanity greatly interfere in multiple social issues, slowing down the pace of life for all of humanity, creating changes in structure and in health and economic system policies.